2013
DOI: 10.1002/nau.22393
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA injection therapy in men with LUTS due to primary bladder‐neck dysfunction: Objective and patient‐reported outcomes

Abstract: BoNT-A injection therapy appears effective and safe in medically refractory men with PBND, although repeated procedures are required for long-term sustained benefit. Randomized controlled trials are warranted in order to corroborate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 26 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…66 Injection of 100 units of BoNTA into the prostatic urethra and bladder neck provided significant improvements in symptom scores, Q max and PVR volume in patients with primary BND and videourodynamically proven obstruction. [67][68][69] These preliminary results suggest that BoNTA improves LUTD in men, probably by modulating the adrenergic sympathetic nerves or sensory pathways.…”
Section: Bph and Male Lutsmentioning
confidence: 73%
“…66 Injection of 100 units of BoNTA into the prostatic urethra and bladder neck provided significant improvements in symptom scores, Q max and PVR volume in patients with primary BND and videourodynamically proven obstruction. [67][68][69] These preliminary results suggest that BoNTA improves LUTD in men, probably by modulating the adrenergic sympathetic nerves or sensory pathways.…”
Section: Bph and Male Lutsmentioning
confidence: 73%
“…Poor bladder neck relaxation in BND may lead to weak stream and increased residual urine amount after voiding [63]. Recent studies demonstrated that BoNT-A injections in the external urethral sphincter, pelvic floor muscle, or bladder neck may offer promising therapeutic effects for DV symptoms improvement [61,64,65]. Synchronous significant reduction of the bladder outlet resistance and the pelvic floor pressure were observed in a study after BoNT-A injection treatment to the pelvic floor muscle, which indicates a more complex mechanism in DV symptoms.…”
Section: Bont-a Injection For Dysfunctional Voiding (Dv) or Bladder Nmentioning
confidence: 99%
“…IC/BPS is a clinical syndrome described as having "An unpleasant sensation (pain, pressure, discomfort) perceived to be related to urinary bladder, associated with lower urinary tract symptoms of more than 6 weeks duration, in the absence of infection or other identifiable causes" [62]. Though the real pathophysiology of IC/BPS has remained unclear for decades, recent studies have progressed in molecular biology, which have focused on urothelial dysfunction and neurogenic inflammation and could explain some part of the disease [61][62][63][64][65][66]. Urothelial defect with surface glycosaminoglycan and associated dysregulation of urothelial permeability has been established as one of the pathogenesis of IC/BPS [65].…”
Section: Bont-a Injection For Ic/bpsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several theories regarding the etiology of PBNO, including muscular and neurologic dysfunction and fibrosis [5]. While medical treatment of the condition includes the use of α-blockers and the injection of agent such as onabotulinumtoxin A [6], the most common treatment is the surgical approach of transurethral incision [7] which is the treatment of choice for patients refractory to medical approaches. Despite a success rate of the surgical treatment for the disorder as high as 87% [7], the outcome remains unsatisfactory for a significant proportion of patients for whom pre-operative urodynamic studies failed to provide useful guidance for treatment.…”
Section: Introductionmentioning
confidence: 99%